2019
DOI: 10.1371/journal.pmed.1002973
|View full text |Cite
|
Sign up to set email alerts
|

Opioid agonist treatment scale-up and the initiation of injection drug use: A dynamic modeling analysis

Abstract: Background Injection drug use (IDU) is associated with multiple health harms. The vast majority of IDU initiation events (in which injection-naïve persons first adopt IDU) are assisted by a person who injects drugs (PWID), and as such, IDU could be considered as a dynamic behavioral transmission process. Data suggest that opioid agonist treatment (OAT) enrollment is associated with a reduced likelihood of assisting with IDU initiation. We assessed the association between recent OAT enrollment and assisting IDU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 87 publications
(120 reference statements)
0
24
1
Order By: Relevance
“…We are interested in understanding the extent to which opioid agonist treatment enrollment and other factors are associated with assisting injection drug use initiation. The following describes part of what we recently found, using a conventional SOCS approach (Marks et al, 2019):…”
Section: Example: Factors Related To Injection Drug Use Initiation Assistancementioning
confidence: 95%
See 3 more Smart Citations
“…We are interested in understanding the extent to which opioid agonist treatment enrollment and other factors are associated with assisting injection drug use initiation. The following describes part of what we recently found, using a conventional SOCS approach (Marks et al, 2019):…”
Section: Example: Factors Related To Injection Drug Use Initiation Assistancementioning
confidence: 95%
“…Using data from a multi-site prospective cohort study, we investigated factors that were associated with providing injection assistance to previously injection-naïve individuals the first time they injected (Marks et al, 2019). Most initiations (i.e., the first time an injection-naïve person injects drugs) are facilitated by other people who inject drugs (PWID).…”
Section: Example: Factors Related To Injection Drug Use Initiation Assistancementioning
confidence: 99%
See 2 more Smart Citations
“…Opioid agonist treatment may have important collateral health effects as well. Analyzing data from a 3-country (i.e., Canada, the US, and Mexico) cohort of people who inject drugs [3638], Charles Marks and colleagues [39] found that people who inject drugs and who receive opioid agonist treatment are approximately half as likely to assist others in initiating injection drug use. They then developed a deterministic, dynamic transmission model of initiation into injection drug use, ongoing drug use, and cessation of drug use.…”
Section: Interventions To Reduce the Harms Associated With Opioid Usementioning
confidence: 99%